1994
DOI: 10.1128/jcm.32.1.28-31.1994
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Taiwan variant of Epstein-Barr virus in throat washings from patients with head and neck tumors in Taiwan

Abstract: The prevalence of the Epstein-Barr virus (EBV) Taiwan variant was investigated in the throat washing (A1W) samples from patients with head and neck tumors, persons with nonmalignant diseases, and healthy adults in Taiwan. By using the EBV (BNLF-1 gene)-specific primers and PCR, the EBV latent membrane protein gene BNLF-1 was detected in 91 (61%,b) of the 150 TW samples from patients with tumors, including 25 (78%) of 32 patients with nasopharyngeal carcinoma and 66 (56%o) of 118 other patients with head and ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 17 publications
1
22
0
Order By: Relevance
“…This polymorphism was also present in NPC from Alaska and in some of the NPC samples from Caucasian Americans but was absent in NPC and healthy controls in Africa [ 19 , 37 ]. The loss of an Xho I restriction site has been associated with Chinese NPC, and it has been considered to be a specific tumour marker in NPC biopsies and throat washes [ 18 , 21 , 27 , 38 ]. However, to date, little is known about the efficiency of malignant transformation by this variant.…”
Section: Discussionmentioning
confidence: 99%
“…This polymorphism was also present in NPC from Alaska and in some of the NPC samples from Caucasian Americans but was absent in NPC and healthy controls in Africa [ 19 , 37 ]. The loss of an Xho I restriction site has been associated with Chinese NPC, and it has been considered to be a specific tumour marker in NPC biopsies and throat washes [ 18 , 21 , 27 , 38 ]. However, to date, little is known about the efficiency of malignant transformation by this variant.…”
Section: Discussionmentioning
confidence: 99%
“…The XhoI loss is commonly reported in Southern Asiatic populations where the vast majority of NPC cases harbored this variation [Khanim et al, 1996;Han et al, 2003;See et al, 2008;Feederle et al, 2015]. Literature refers that the loss of a XhoI restriction site might be considered a specific tumor marker for NPC [Hu et al, 1991;Chen et al, 1992;Jeng et al, 1994;Chang et al, 1995;Tan et al, 2003;See et al, 2008], and in fact, a recent meta-analysis confirmed that there is a strong association between the XhoI-loss and NPC development, especially in Asia [da Costa et al, 2015]. Yet, this variation is almost absent in NPC cases from North of Africa [Bouzid et al, 1994;Henry et al, 2001;Ayadi et al, 2007].…”
Section: Variations In Ebv Genomementioning
confidence: 99%
“…Furthermore, to date, very little is known about the biological role of this variant in the transformation efficiency of EBV [See et al, 2008]. Cheung et al [1996] China NPC 5 5 (100) Chang et al [1995] Taiwan NPC 48 48 (100) Bouzid et al [1994] North Africa (region) NPC 13 1 (7.7) Jeng et al [1994] Taiwan NPC 32 25 (78.1) Abdel-Hamid et al [1992] Multicenter NPC 51 33 (64.7) Hu et al [1991] Multicenter NPC 56 38 (67.9) aHSCT, allogeneic hematopoietic stem cell transplanted; HSNCC, head and neck squamous cell carcinoma; NPC, nasopharyngeal carcinoma; GC, gastric carcinoma; IM, infectious mononucleosis; HL, Hodgkin lymphoma; LELC, lymphoepithelioma-like carcinoma.…”
Section: Variations In Ebv Genomementioning
confidence: 99%
“…Detection of EBV genomic DNA in a nasopharyngeal biopsy specimen may indicate the presence of NPC 9. It has been reported that 3 latent membrane proteins are expressed in NPC and that nearly all NPC tumor cells contain the EBV‐derived latent membrane protein 1 ( LMP‐1 ) gene 11, 12. LMP‐1 is a phosphoprotein in vivo 13.…”
mentioning
confidence: 99%